New Concepts of Psychostimulant Induced Neurotoxicity - Sharma, H. S. (Hari Shanker) (International review of neurobiology, 2009)
Published since 1959, International Review of Neurobiology is a well-known series appealing to neuroscientists, clinicians, psychologists, physiologists, and pharmacologists. Led by an internationally renowned editorial board, this important serial publishes both eclectic volumes made up of timely reviews and thematic volumes that focus on recent progress in a specific area of neurobiology research. With recent advancements in new knowledge, it has become evident that psychostimulants and related drugs of abuse are influencing our central nervous system (CNS) remarkably and could alter their function for long-time. This volume is the first to focus on substance abuse induced brain pathology in widest sense as it covers alterations in neuronal, glial and endothelial cell functions under the influence of acute or chronic usage of substance abuse.